Correlation Between Systemic Immune-Inflammation Index and Depression in Patient with Heart Failure Reduced Ejection Fraction in Sardjito Hospital Yogyakarta - Somba, Imanuel Maryo; Sofia, Noor Asyiqah; Anggraeni, Vita Yanti (Acta Interna The Journal of Internal Medicine, 2024)
Background. Depression is highly prevalent in patients with heart failure reduced ejection fraction (HFrEF). The pathophysiology between these two conditions is related to the inflammation process, therefore some inflammatory markers can be used to assess those conditions. In recent years, the systemic immune-inflammation index (SII) has been developed as a simple and inexpensive indicator of inflammation. Unfortunately, we did not find any study that assessed the correlation between SII and depression in patients with HFrEF.Objective. To investigate the correlation between SII and depression in patients with HFrEF in Sardjito Hospital YogyakartaMethods. This was a cross-sectional study on patients with HFrEF in Sardjito Hospital between February 2023 and May 2023. The normality test was carried out using the Shapiro-Wilk test. Bivariate analysis was carried out using the Spearman correlation test. The result was considered statistically significant when p-value <0.05. Multivariate analysis was carried out using multiple linear regression test.Results. There were 47 HFrEF patients with depression. There was a significant relationship between SII and depression scores from the Spearman Correlation test results of SII with depression scores, with p=0.009. The result showed that the higher the SII, the higher the depression score. The correlation coefficient between the two variables was r=0.375, showing that the correlation was in the weak category.Conclusion. There is a positive correlation between the systemic immune-inflammation index and depression in patients with heart failure reduced ejection fraction.